(untitled) (Sebha University Conference Proceedings, 2024)
In this study , the types of solid waste disposed of in the city of Ajdabiya were identified , and the Causes of their accumulation and the methods used to reduce or Completely get rid of them by distributing survey form the field is on Residential neighborhoods of Ajdabiya City , and data Collection through field Visits and taking photos photo illustration, plan addition to the survey form of the Competent authority Ajdabiya municipality , where arrived this study to bifurcate the Composition of Solids waste with clear predominance of nutrient and Organic Residues from the rest ingredients , where the percentage of food waste reached 72,7%which is the highest percentage among the types of solid waste collected, we have a good efficiency for the incompatibility of the number of Containers , as well as the process of collecting and transfeming , the calls there is a consensus in some population inflation in modesty and increase the number of residential neighborhoods in the city of Ajdabiya , as the is also a lack of consistency it times between citizens taking out their waste and the time of transport trucks passing by , in addition to the lake of follow up continuous field Collection and transportation workers .